Effectivity of Squat to Stand Training in Improving Lower Extremity Muscle Power on Children with Down Syndrome - Syaahidah, Habiibatusy; Widodo, Agus; Hidayati, Atik (Universitas Muhammadiyah Surakarta, 2022)
Background: Squat to stand training is one of the core muscle and lower extremity muscle strengthening exercises that aim to improve lower extremity muscle power to prepare foot muscle in the standing process.Objective: This study aims to find the effectiveness of squat-to-stand training on a down syndrome patient aged 19 months.Method: This study is single-subject research on a Down Syndrome patient aged 19 months old with walking delay, hypotonia on both legs, unable to stand independently, and muscle weakness on both lower extremities. The subject had received squat-to-stand training for four weeks, twice a week, and a follow-up at each end of the session.Result: there is an improvement in XOTR assessment, where the baseline result was T that interpreted as the presence of muscle contraction with minimum movement, and after four weeks of intervention, there is an improvement in the muscle tone and movement compared with the baseline though have not met the X value yet, with normal muscle power interpretation.Conclusion: squat-to-stand training is practical but does not significantly improve lower extremity muscle power in Down Syndrome patients.